Early results of complete subtalar release in congenital clubfoot deformity - Karakurt, Lokman; Yilmaz, Erhan; Inci, Murat; Serin, Erhan; Oztürk, Mehmet (My University, 2003)
OBJECTIVES: We evaluated the radiological and clinical results of complete subtalar release in patients with congenital clubfoot deformity. METHODS: We performed complete subtalar release in 30 feet of 20 patients (14 boys, 6 girls; mean age 8 months; range 3.5 to 18.5 months). We employed the Cincinnati incision in all cases. The results were evaluated according to the Simon's clinical and radiological criteria. Tarsal bone problems were analyzed separately. The mean follow-up period was 24.6 months (range 12 to 41 months). RESULTS: Clinical results were satisfactory in 24 feet (80%) and unsatisfactory in six feet (20%). Radiologically, satisfactory and unsatisfactory results were encountered in 19 feet (63%) and 11 feet (37%), respectively. Undercorrection occurred in 13 feet (43.3%) and overcorrection in one foot (1.4%). Revision surgery which was recommended for five undercorrected feet (16.6%) with unsatisfactory clinical and radiological results could be performed in four feet (13.3%). Deep skin necrosis that occurred in two feet (one with Achilles tendon necrosis) was treated surgically. Superficial skin necrosis developed in five feet and soft tissue infection in one feet, all of which responded well to conservative treatment. Other complications included talar head hypoplasia and navicular hypoplasia in two feet, respectively. CONCLUSION: Complete subtalar release allows to correct all components of clubfoot deformity in a single session. The results may appreciably be improved with enhanced surgical experience.
Doguştan çarpik ayakli olgularda komplet subtalar gevşetme uygulamalarimizin erken dönem sonuçlari.
Keywords: Clubfoot; Female; Humans; Infant; Male; Orthopedic Procedures; Range of Motion, Articular; Subtalar Joint; Tendons; Treatment Outcome; article; clubfoot; evaluation; female; human; infant; joint characteristics and functions; male; orthopedic surgery; radiography; subtalar joint; tendon; treatment outcome